Ragam Bahasa Gaul “Jaksel” terhadap Penggunaan Bahasa Indonesia di Media Sosial “Instagram” - Ia Rusiani (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
In this day and age, social media has become one of the important platforms for communication, especially among young people. One of the phenomena that has emerged is the use of slang, especially from the South Jakarta area, which combines elements of Indonesian and English. This study aims to explore how this variety of slang affects the way people communicate on social media. By understanding this influence, it is hoped that we can see changes in the good and correct use of Indonesian among the use of Instagram social media.